Structural optimisation approach and indicators for integrated municipal solid waste management - Tan, Sie Ting (2015)
Rapid urbanization, population growth, and industrialization are contributing to the large-scale increase of total waste generation in Malaysia and changing the characteristics and composition of the municipal solid waste (MSW). The present practice of municipal solid waste management (MSWM) in Malaysia is depends very much on landfill disposal. To date, Malaysia is at the transition and planning stage towards sustainable MSWM with more efficient approaches. The main aim of this thesis is to develop a sustainable MSMW system based on a structural and comprehensive framework through optimisation modeling and indicator approaches. A case study of Iskandar Malaysia (IM) was employed in this research. In order to achieve the goal, three objectives were identified: the first objective is to evaluate and benchmark the performance of the MSWM system through a new developed indicator system known as Sustainable Waste Management Performance Indicator (SWMPI). The second objective is to assess the energy and carbon reduction potential of waste-to-energy (WTE) strategies for MSW in IM. The results in the second objective were used as the input data for the third objective. The third objective is to establish a sustainable and cost effective solution for the processing network of MSWM, through the model of Optimal Waste Processing Network (OWPN). At the end of the study, improvement of MSMW system through the third objective had been evaluated by the model of SWMPI from first objective. The analysis has proven that the optimal results from the OWPN model of MSWM system has successfully improved the waste management in terms of waste basic data, economic, waste management, and environmental criteria in SWMPI, where significant improvement was found in waste management and environment criteria of the indicator system. Both SWMPI and OWPN had been proven as powerful tools that assist the benchmarking of MSWM system in IM against other cities